2020
DOI: 10.1093/jcbiol/ruaa052
|View full text |Cite
|
Sign up to set email alerts
|

Depth and productivity as predictive parameters for the widespread invasion of Arctodiaptomus dorsalis (Marsh, 1907) (Copepoda: Calanoida) in tropical lakes in the Philippines

Abstract: A massive invasion of the Neotropical calanoid copepod Arctodiaptomus dorsalis (Marsh, 1907) has been taking place in the Philippines since at least 1993. This copepod’s fecundity is known to depend on food concentration, increasing temperature appears to have detrimental effects on its hatching success and survivorship, but parameters that are truly predictive of the successful integration and propagation of this species in particular bodies of water have not yet been identified. We conducted a spatial analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…As reported in previous studies, such conditions present the ideal environment for the propagation of the Invasive A. dorsalis, as it prefers and thrives in eutrophic waters (Elmore 1983;Tordesillas et al 2018;de Leon et al 2020).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…As reported in previous studies, such conditions present the ideal environment for the propagation of the Invasive A. dorsalis, as it prefers and thrives in eutrophic waters (Elmore 1983;Tordesillas et al 2018;de Leon et al 2020).…”
Section: Discussionmentioning
confidence: 60%
“…According to Elmore (1983) and Tordesillas et al (2018), A. dorsalis can only survive in aquatic environments with high nutrient concentration, establishing its preference towards eutrophic waters. de Leon et al (2020) also reported that one of the largest, based on mean TL, and most fecund A. dorsalis was obtained from the same lake when they compared populations obtained from lakes located in South Luzon, Philippines. The second largest and most fecund ovigerous females, on the other hand, was obtained from Lake Sampaloc (mean PL = 0.87 mm; mean CS = 9.87 eggs female -1 ), the third shallowest lake among the sampling sites.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our study lakes, it has been reported that zooplankton communities are dominated by a calanoid copepod, A. dorsalis, which has become a common species in Philippine inland waters (Papa et al, 2012;De Leon et al, 2020). A. dorsalis is known as a selective phytoplankton grazer that prefers diatoms over cyanobacteria and green algae among phytoplankton assemblages (Cisneros et al, 1991).…”
Section: Discussionmentioning
confidence: 78%